Analysis Of Plyometric Training In Volleyball: Systematic Literature Review - Wibowo, Sherwin Mahardika; S, Adi (UNIVERSITAS NEGERI MAKASSAR, 2025)
The purpose of this research is to look into the use of Plyometric Training in Volleyball. Materials and methods: The table PRISMA will be used for the systematic review and meta-analysis in this review investigation. Various studies were published from January 2020 to December 2024. In the search procedure, the following keywords were used: (1) Plyometric; (2) Training; (3) Volleyball. The search in the study used Scopus research journal databases. The theme of this research as a whole obtained 117. Contains 41 articles, of which 10 are relevant. Analysis of plyometric training in volleyball includes the effect of plyometric exercises based on relevant results, including increasing vertical jumps, changing the direction of the jump, completing the training program, increasing leg muscle strength, increasing explosive jumps, and improving performance (serve, smash, and block).